Journalism from Above: Drones and the Media in Critical Perspective - Harvard, Jonas (2020)
In the last decade, the development of small, remotely operated multicopters with cameras, so-called drones, has made aerial photography easily available. Consumers and institutions now use drones in a variety of ways, both for personal entertainment and professionally. The application of drones in media production and journalism is of particular interest, as it provides insight into the complex interplay between technology, the economic and legal constraints of the media market, professional cultures and audience preferences. The thematic issue Journalism from Above: Drones, the Media, and the Transformation of Journalistic Practice presents new research concerning the role of drones in journalism and media production. The issue brings together scholars representing a variety of approaches and perspectives. A broad selection of empirical cases from Finland, Spain, Sweden, the UK and the US form the basis of an exploration of the changing relations between the media, technology and society. The articles address topics such as: Adaption of drone technology in the newsrooms; audience preferences and reactions in a changing media landscape; the relation between journalists and public authorities who use drones; and attitudes from journalistic practitioners as well as historical and future perspectives.